The Municipal Council of Tunis, 1858–1870: A Study in Urban Institutional Change - Cleveland, William L. (International Journal of Middle East Studies, 1978)
Throughout the nineteenth century, the cities on the southern and eastern shores of the Mediterranean, Tunis, Alexandria, Beirut, Smyrna, and Istanbul among them, experienced an influx of foreign communities which, combined with an increase in the indigenous populations and new urban policies on the part of certain rulers, tended to disrupt customary patterns of urban relationships. Although the scholarship of recent years has provided a new awareness of the network of interrelationships which held together the segments of medieval Islamic urban society, studies on the nineteenth-century changes in those relationships as represented by the policies of Muhammad ῾Alī, Aḥmad Bey, and the Ottoman Tanzimat reformers, have tended to focus more on aspects of state and government than on cities as such. Yet cities, especially capital cities, reflect most intensely periods of social and institutional transition.
Keywords: Emigration -- Mzab -- Tunisie